Can small farms benefit from big companies' initiatives to promote mechanization in Africa? A case study from Zambia. (April 2019) - Adu-Baffour, Ferdinand; Daum, Thomas; Birner, Regina
Highlights: Private-sector initiatives can benefit smallholder farmers. Users of tractor services almost doubled their income by cultivating more land. Yields increased but income per hectare did not increase significantly. Demand for hired labor increased due to land expansion and a reduction of family labor. Abstract: After years of neglect, there is a renewed interest in agricultural mechanization in Africa. Since government initiatives to promote mechanization are confronted with major governance challenges, private-sector initiatives may offer a promising alternative. However, given limited scientific studies on such private-sector options such approaches are often viewed skeptically. One concern is that multi-national agribusiness companies take advantage of smallholder farmers. Another concern is that mechanization causes rural unemployment. To shed light on these concerns, this paper analyzes an initiative of the agricultural machinery manufacturer John Deere to promote smallholder mechanization in Zambia through a contractor model. The analysis focuses on the impact of this initiative on farmers who receive tractor services using Propensity Score Matching. The results indicate that farmers can almost double their income by cultivating a much larger share of their land. The analysis suggests that the increased income is used for children's education and more food, but does not result in increased food diversity. The demand for hired labor increases due to land expansion and due to a shift from family labor, including that of children, to hired labor. Questions that require further investigation are identified, including strategies to incentivize tractor owners to provide services, to also increase land productivity, and to avoid new forms of dependency of agricultural laborers that may result from a shift in the timing of the labor demand.